Acute on Chronic Venous Thromboembolism on Therapeutic Anticoagulation. (8th October 2013) - Bassi, Byron; Nickels, L. Connor; Flach, F. Eike; DePortu, Guiliano; Ganti, Latha
Abstract : A case of proximal venous thromboembolism in a patient who presented to the ED with lower extremity pain is presented. Making this diagnosis is very important as fifty percent of patients with symptomatic proximal DVTs will go on to develop PE without treatment. This report underscores the utility of bedside ultrasonography in the emergency department.